P443 Clinical features, therapeutic requirements, and evolution of patients with Crohn's disease and upper digestive tract involvement (CROHNEX study). (25th January 2019) - Sainz Arnau, E; Zabana, Y; Miguel, I; Fernández Clotet, A; Casanova, M J; Martín, M D; Picó, M D; Alfambra, E; Rodriguez, I; Muñoz, F; Domínguez, M; Iglesias, E; et al.
Abstract: Background: Patients with upper (L4) and diffuse (L1 + L4) Crohn's disease (CD) may have a more aggressive and refractory disease course. However, evidence on this particular sub-type of patients is scarce. Clinical guidelines do not offer specific protocols on how to manage them. Methods: To identify the clinical characteristics, therapeutic requirements and complications that are independently associated with an upper digestive tract CD involvement. METHODS: Retrospective study of cases and controls matched (1: 2) by sex and age in patients with CD (L4 or L1 + L4: cases; L1 or L3: controls) of the ENEIDA database (49 hospitals). The small intestine was evaluated with radiologic and/or endoscopic examination, and complex perianal disease was excluded. Clinical variables: pattern, severity, anaemia; Complications: stenosis, fistula, abscess, perforation and digestive bleeding; Therapeutic requirements: use of 1 anti-TNF, more than 1 ant-TNF, anti-TNF intensification, second-line biologic drug, iv iron, blood transfusions, enteral nutrition, endoscopic/radiological treatments, surgeries and hospitalisations were investigated. A logistic regression analysis with those significant variables in univariate analysis (SPSS) was performed. Results: In total, 919 cases and 1838 controls were identified. Multi-variate analysis showed that cases were independently associated to stricturing pattern at diagnose (OR: 1.2, 95% CI: 1–1.5; p = 0.048), iron deficient anaemia (OR: 2.3, 95% CI: 1.6–3.4; p < 0.0001), more extensive involvement ( > 30 cm) (OR: 2.7, 95% CI: 2.3–3.3; p <0.0001), and the use of second-line biologics during follow-up (OR 1.6, CI 95% 1–2.4; p = 0.04). In contrast, they exhibit less abscesses (OR 0.6, 95% CI: 0.5–0.8; p = 0.001) and have less familial history of inflammatory bowel disease (OR 0.7, 95% CI: 0.6 −0.9; p = 0.008). Conclusions: In the most extensive series of upper digestive tract involvement in CD, it is shown that they present a more advanced disease at CD diagnosis, suggesting either a late diagnosis or different physiopathologic pathways for L4 involvement. Consequently, they are more refractory to treatments, requiring more frequently second-line biologics. A specific diagnostic and therapeutic strategy must be considered for these patients. This includes consider signs that allow a high rate of suspicion such as iron deficient anaemia in patients with normal upper and lower endoscopy.